Presentation - Alvarado-Sánchez, Meylin (Revista Geográfica de América Central., 2024)
The Geographic Journal of Central America celebrates its 50th anniversary as an academic leader in the dissemination of geographic and related scientific studies in Costa Rica and globally. Led by the School of Geographic Sciences at the National University and published by the National University Press (EUNA) since 1974, this journal has been a platform for discussion and contributions from geographers, students, and professionals interested in land management, natural resource management, and regional studies technologies. On this special anniversary, we reaffirm our commitment to providing high-quality research in Spanish, English, and Portuguese, aiming to enrich knowledge and highlight the contribution of geography to today’s society.